Penganggaran Berbasis Kinerja dan Optimasi Pelayanan Publik: Tinjauan Literatur Sistematis di Bidang Imigrasi - Alfath Akbar; Wisnu Widayat; Mochammad Ryanindityo (Pusat Riset dan Inovasi Nasional, 2025)
Performance-Based Budgeting (PBB) is a financial management approach in the public sector that links budget allocations with measurable performance outcomes and service effectiveness. In the immigration sector, PBB is an important instrument for enhancing spending efficiency, transparency, and the quality of public services. This study employs a Systematic Literature Review (SLR) to analyze practices, strategies, and challenges in implementing PBB within immigration institutions. The review covers articles published between 2013 and 2023 from databases such as SINTA, DOAJ, and Google Scholar, with inclusion criteria focusing on public sector budgeting and its relevance to immigration administration. The findings indicate that the successful implementation of PBB depends on measurable performance indicators, strong managerial commitment, and active participation of organizational actors in budget planning and evaluation. However, several challenges were identified, including bureaucratic resistance, weak performance measurement systems, and limited fiscal capacity at the operational level. To overcome these barriers, the study highlights the need for strengthened leadership commitment, improved accountability frameworks, and the development of integrated digital systems to enable real-time monitoring. By optimizing the Public Work Plan (PBK), immigration services are expected to manage resources more efficiently, respond to global dynamics, and improve services for both citizens and foreigners.